2017
DOI: 10.1016/j.scr.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The administration of multipotent stromal cells at precancerous stage precludes tumor growth and epithelial dedifferentiation of oral squamous cell carcinoma

Abstract: Multipotent stromal cells (MSCs) are envisioned as a powerful therapeutic tool. As they home into tumors, secrete trophic and vasculogenic factors, and suppress immune response their role in carcinogenesis is a matter of controversy. Worldwide oral squamous cell carcinoma (OSCC) is the fifth most common epithelial cancer. Our aim was to determine whether MSC administration at precancerous stage modifies the natural progression of OSCC. OSCC was induced in Syrian hamsters by topical application of DMBA in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…As tumor growth restriction was not an expected outcome of the present work, our original study design did not consider exploration of the putative mechanisms behind it. Previously, we showed that local administration of allogeneic MSCs at dysplasia or papilloma stage precludes OSCC tumor growth (unpublished results, [ 19 ]). While at dysplasia stage MSCs impede mast cell infiltration and diminish tissue vascularization, at papilloma stage donor cells diminish proliferation, increase apoptosis, and reduce epithelial dedifferentiation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As tumor growth restriction was not an expected outcome of the present work, our original study design did not consider exploration of the putative mechanisms behind it. Previously, we showed that local administration of allogeneic MSCs at dysplasia or papilloma stage precludes OSCC tumor growth (unpublished results, [ 19 ]). While at dysplasia stage MSCs impede mast cell infiltration and diminish tissue vascularization, at papilloma stage donor cells diminish proliferation, increase apoptosis, and reduce epithelial dedifferentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Images were captured with a digital camera (DFC295; Leica). Samples were classified as hyperplasia, dysplasia, papilloma, or carcinoma as described previously [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were classified according to the revised criteria given by the World Health Organization (2005). Three independent observers performed histological analyses blind; one of them is a pathologist expert in oral diseases (42,43).…”
Section: Histopathologicalanalysismentioning
confidence: 99%
“…Five representative optical sections by sample (n=6/group) were photographed using 60X magnification. The images obtained per field of each sample, were processed with the same conditions and the positive protein signal (pixels intensity) was analyzed and quantified using Fiji Image J software (NIH, USA) (42,43).…”
Section: Immunohistofluorescenceanalysismentioning
confidence: 99%